Black wattle (Acacia mearnsii) condensed tannin extract as feed additive in diets of weaned piglets Tanino condensado de acácia-negra (Acacia mearnsii) como aditivo nutricional em dietas de leitões desmamados - Schneider L.I. (2024)
© 2024, Universidade Federal de Santa Maria. All rights reserved.This study evaluated the effect of black wattle (Acacia mearnsii) condensed tannin extract in simple and complex diets for weaned piglets on performance, faecal consistency and serum haptoglobin concentrations. Eighty-eight female and castrated male piglets were used, weaned at 28 ± 3 days old, with an initial body weight of 8.02 ± 1.21 kg, housed in same-sex pairs and distributed in four treatments in a 2 x 2 factorial experiment in a randomised complete block design. The experimental treatments were simple diet (SD), simple diet + tannin (SD+T), complex diet (CD) and complex diet + tannin (CD+T). The simple diets contained lower concentrations of dairy ingredients, inclusion of barley and no addition of zinc oxide, palatant, acidifier and yeast. The diets with tannin were supplemented with 1,850 mg kg-1 of black wattle condensed tannin extract. The feed programme consisted of three diets: Pre-starter I (0–7 days), Pre-starter II (8–21 days) and Starter (22–28 days). Feed and water were available ad libitum. Body weight and feed intake were measured weekly to calculate the average daily feed intake, daily weight gain and feed conversion ratio. The faecal consistency score was measured daily to calculate the diarrhoea occurrence percentage. Blood samples for serum haptoglobin concentration were collected at 7 and 14 days after weaning. The addition of condensed tannin had no effect (P > 0.05) on evaluated performance variables for weaned piglets. The diet type also did not affect the piglets’ performance (P > 0.05). The inclusion of black wattle (Acacia mearnsii) condensed tannin does not affect piglet performance, reduces the incidence of diarrhoea in the first week after weaning and decreases the haptoglobin inflammatory response.